School-related problems of agriculture students at the University of Southeastern Philippines implications for student personnel services - Esteves, Rodulfo Pimentel 1952-
The author investigated the school-related problems of agriculture students and the implications for student personnel services at the College of Arts and Sciences at the University of Southeastern Philippines during the first semester of school year 1981-1982.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Personnel service in higher education -- Philippines; Davao City